2017
DOI: 10.1002/1873-3468.12722
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer‐derived exosomes promote peritoneal metastasis by destroying the mesothelial barrier

Abstract: An intact mesothelium serves as a protective barrier to inhibit peritoneal carcinomatosis. Cancer‐derived exosomes can mediate directional tumor metastasis; however, little is known about whether gastric cancer‐derived exosomes will destroy the mesothelial barrier and promote peritoneal dissemination. Here, we demonstrate that gastric cancer‐derived exosomes facilitate peritoneal metastasis by causing mesothelial barrier disruption and peritoneal fibrosis. Injury of peritoneal mesothelial cells elicited by gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 53 publications
0
77
0
Order By: Relevance
“…Exosomes have been reported to play important roles in gastric cancer and have the potential to be used as ideal biomarkers for gastric cancer diagnosis, prognosis and therapy. Gastric cancer derived exosomes facilitate peritoneal metastasis by disrupting mesothelial barrier and inducing peritoneal fibrosis . Exosomes secreted from gastric cancer cells deliver EGFR to regulate liver microenvironment, promoting gastric cancer liver metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes have been reported to play important roles in gastric cancer and have the potential to be used as ideal biomarkers for gastric cancer diagnosis, prognosis and therapy. Gastric cancer derived exosomes facilitate peritoneal metastasis by disrupting mesothelial barrier and inducing peritoneal fibrosis . Exosomes secreted from gastric cancer cells deliver EGFR to regulate liver microenvironment, promoting gastric cancer liver metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes containing active proteases are able to induce ECM degradation, and they contribute to ECM remodeling by selectively or directly binding to the ECM‐binding motif presented on exosomal surface adhesion proteins, which enhances fibroblast adhesion and migration . Gastric cancer‐derived exosomes facilitate peritoneal metastasis by causing mesothelial barrier disruption and peritoneal fibrosis through concurrent apoptosis and MMT . Similar to primary tumor sites, TDEs also participate in the conversion of fibroblasts to CAFs phenotype within the pre‐metastatic niche, thus facilitating cancer metastasis.…”
Section: Exosomes In Sequential Processes Of Tumor Metastasismentioning
confidence: 99%
“…97 Gastric cancer-derived exosomes facilitate peritoneal metastasis by causing mesothelial barrier disruption and peritoneal fibrosis through concurrent apoptosis and MMT. 98 Similar to primary tumor sites, TDEs also participate in the conversion of fibroblasts to CAFs phenotype within the pre-metastatic niche, thus facilitating cancer metastasis. In HCC, highmetastatic cells secrete exosomal miR-1247-3p that directly targets B4GALT3, leading to activation of β1-integrin-NF-κB signaling in fibroblasts.…”
Section: Exosomal Integrin Model Only Until 2015 Hoshino Et Almentioning
confidence: 99%
“…Deng et al (38) pretreated nude mice with MGC803 cell-derived exosomes and injected MGC803 cells into the abdominal cavity, and observed that the total weight of the tumor nodules was significantly increased compared with in PBS-treated mice in vivo. Mesothelial cells (HMrSV5) were also cultured with exosomes, which revealed that exosomes induced injury of peritoneal mesothelial cells by promoting apoptosis and MMT, via upregulation of the extracellular signal-regulated kinase pathway (38).…”
Section: Exosomes In Peritoneal Dissemination Of Gastric Cancermentioning
confidence: 99%
“…Mesothelial cells (HMrSV5) were also cultured with exosomes, which revealed that exosomes induced injury of peritoneal mesothelial cells by promoting apoptosis and MMT, via upregulation of the extracellular signal-regulated kinase pathway (38).…”
Section: Exosomes In Peritoneal Dissemination Of Gastric Cancermentioning
confidence: 99%